Organic electroluminescent compound and organic electroluminescent device thereof
By designing an organic electroluminescent compound with an AAD type bipolar structure to be used for the luminescent layer of OLED devices, the problem of low luminescent efficiency of existing OLED devices under high current density is solved, and higher luminescent efficiency is achieved and longer lifespan.
Patent Information
- Application Number
- CN202411769086.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-02-11
AI Technical Summary
Existing OLED devices have low luminescence efficiency under high current density, triplet annihilation accelerates, and the wide energy level distribution of bipolar main materials is insufficient, making it difficult to meet market demand.
An organic electroluminescent compound is designed, and its structure includes azabenzene as the parent core, and the immobilized substituents, electron withdrawing groups and electron donating groups are symmetrically introduced on both sides to form a bipolar host material of the AAD type. This material is used in the luminescent layer of OLED devices, and through fine energy level control and structural stability optimization, the holes and electrons are balanced to form a wide carrier composite region.
It significantly improves the luminous efficiency of OLED devices, reduces the starting voltage and energy consumption, extends the device's working life, and optimizes the internal energy level distribution of molecules.
Smart Images

Figure BDA0005169787770000011 
Figure BDA0005169787770000021 
Figure BDA0005169787770000023
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of organic light-emitting materials and semiconductors, and specifically relates to an organic electroluminescent compound and an organic electroluminescent device thereof. Background Art
[0002] Organic light-emitting diode (OLED) technology, with its unique characteristics of self-luminescence, high brightness, high contrast, thinness, and flexibility, is driving a wave of innovation in the display and lighting sectors. OLED's core competitiveness lies in its manufacturing process and luminescent materials. Currently, the process technology is maturing, significantly improving product performance and cost-effectiveness. However, optimizing and selecting luminescent materials, particularly those with high luminous efficiency and pure color, remains a major challenge.
[0003] OLED devices typically employ a multilayered design, comprising a hole injection layer, a transport layer, an electron injection layer, a transport layer, and the crucial light-emitting layer. The light-emitting layer is composed of a host material and a guest material (dopant). Sensitizers are sometimes added to optimize energy level matching and enhance luminous efficiency. The host material must possess high stability and a suitable energy level structure to promote efficient energy transfer and prevent exciton annihilation at high concentrations.
[0004] Currently, host materials are broadly classified into three categories: hole-transporting, electron-transporting, and bipolar-transporting materials. Using specific host materials results in the formation of charge recombination zones at specific layer interfaces. However, the mismatched carrier mobility and the limited charge recombination zones negatively impact luminescence efficiency. In particular, triplet annihilation is accelerated at high current densities, reducing luminescence efficiency. Common strategies to address this issue include employing dual-emission layers or mixed host materials, but these approaches increase preparation complexity and pose phase separation challenges.
[0005] Bipolar host materials offer unique advantages in OLEDs due to their ability to balance hole and electron transport, simplifying device structure. Currently, the development of bipolar materials with a broad energy level distribution is far from sufficient to meet market demand. Therefore, the development of higher-performance organic electroluminescent compounds is crucial. Summary of the Invention
[0006] The purpose of the present invention is to overcome the above-mentioned deficiencies in the prior art and to provide an organic electroluminescent compound and an organic electroluminescent device thereof.
[0007] To solve the above technical problems, the technical solution of the present invention is: an organic electroluminescent compound, the general structural formula of the organic electroluminescent compound is shown in General Formula 1:
[0008]
[0009] in,
[0010] A and B are independently selected from H, C6-C 40 Aryl or C4~C 40 A and B cannot be selected from H at the same time;
[0011] X is selected from an O atom, an S atom, a substituted or unsubstituted N atom, or a substituted or unsubstituted C atom; Z1, Z2, and Z3 are independently selected from C atoms or N atoms, and there is at least one N atom among Z1, Z2, and Z3;
[0012] L1, L2, L3 are each independently selected from a bond or a phenylene group;
[0013] Y1 and Y2 are independently selected from C6 to C 20 of heterocyclic aromatic hydrocarbons;
[0014] The bonding mode between A and B and the main structure is single bond or ring;
[0015] The ring structures corresponding to A and B are called ring A and ring B, respectively;
[0016] n is 0 or 1. When n is 0, ring A and ring B are directly bonded to each other via a single bond or are not bonded to each other.
[0017] Preferably, the general formula 1 includes general formula 1-1, general formula 1-2, general formula 1-3, general formula 2-1, general formula 2-2 and general formula 2-3, and the specific general formulas are as follows:
[0018]
[0019] In general formula 1-1, general formula 1-2 and general formula 1-3, the wavy line It indicates that ring A and ring B are directly bonded via a single bond or not.
[0020] Preferably, Y1 and Y2 are independently selected from the group consisting of the following groups:
[0021]
[0022] Preferably, the organic electroluminescent compound is selected from any one of the following 1-series compounds, 2-series compounds, and 3-series compounds:
[0023]
[0024]
[0025]
[0026]
[0027]
[0028]
[0029]
[0030]
[0031]
[0032]
[0033]
[0034]
[0035]
[0036]
[0037]
[0038]
[0039]
[0040]
[0041]
[0042] An organic electroluminescent device comprises a cathode, an anode, and an organic layer located between the cathode and the anode, wherein the organic layer comprises a hole transport layer, a light-emitting layer, and an electron transport layer, wherein the light-emitting layer comprises a host light-emitting material and a guest light-emitting material, wherein the host light-emitting material comprises any one of the organic electroluminescent compounds; and wherein the ratio of the host light-emitting material to the guest light-emitting material is 97:3 to 99:1.
[0043] Preferably, the light-emitting layer includes a host light-emitting material, a guest light-emitting material and a sensitizer material, and the sensitizer material includes any one of the organic electroluminescent compounds; the mass ratio of the host light-emitting material, the sensitizer and the guest light-emitting material is 98:0.1:2.
[0044] Preferably, the guest luminescent material is selected from any one of the following structures:
[0045]
[0046] Preferably, the host luminescent material is selected from any one of the following structures:
[0047]
[0048] Preferably, the ratio of the host luminescent material to the guest luminescent material is 98:2.
[0049] Preferably, the organic electroluminescent device is used in the fields of luminous lighting, image display or photoelectric signal transmission. Compared with the prior art, the advantages of the present invention are:
[0050] (1) The present invention uses azabenzene as the mother core structure and symmetrically introduces fixed substituents on both sides of the mother core, such as phenyl-benzoxazole, phenyl-benzothiazole, phenyl-benzimidazole, phenyl-indole, phenyl-benzoquinoxaline, phenyl-phenanthroline, phenyl-pteridine, etc. This design not only achieves efficient control of the LUMO and HOMO energy levels of the molecule, but also ensures the structural stability of the molecule and effectively regulates the internal energy level distribution of the molecule.
[0051] (1) Through sophisticated molecular structural design, the present invention symmetrically incorporates highly electronegative electron-withdrawing groups (Aceppt) on both sides of the parent azobenzene nucleus, while simultaneously introducing electron-donating groups (Donat) on the opposite side of the azobenzene nucleus. This AAD (Anode-Absorbing-Donating) bipolar host material design ensures an effective balance between electrons and holes in the light-emitting layer, thereby significantly enhancing the device's luminous efficacy.
[0052] (2) The organic electroluminescent compound of the present invention is applied as a bipolar host material to the light-emitting layer of an OLED device, which can effectively balance holes and electrons while forming a wider carrier recombination area, thereby greatly improving the luminous efficiency of the device; at the same time, the organic electroluminescent compound of the present invention is applied as a sensitizer to the light-emitting layer of an OLED device, which has excellent thermal stability and thin film stability, is conducive to the preparation of the device, and significantly improves the luminous efficiency of the device, reduces the starting voltage and energy consumption, and extends the service life of the device. BRIEF DESCRIPTION OF THE DRAWINGS
[0053] (1) Figure 1 , a cross-sectional view of an organic electroluminescent device of the present invention;
[0054] (2) Figure 2 , NMR spectrum of compound 1-1 of the present invention;
[0055] (3) Figure 3 , the nuclear magnetic spectrum of compound 2-19 of the present invention;
[0056] (4) Figure 4 , the nuclear magnetic spectrum of compound 2-59 of the present invention;
[0057] Attachment Figure 1 Marking Description:
[0058] 1. Polymer substrate, 2. Anode layer, 3. Hole injection layer, 4. Hole transport layer, 5. Electron blocking layer, 6. Light-emitting layer, 7. Hole blocking layer, 8. Electron transport layer, 9. Electron injection layer, 10. Cathode layer, 11. Covering layer. DETAILED DESCRIPTION
[0059] The specific embodiments of the present invention are described below with reference to the examples. The raw materials and reagents described in the present invention are all commercially available.
[0060] The synthesis process of the organic electroluminescent compound of the present invention is specifically described as follows:
[0061] The structures of the key intermediates M1 to M27 involved in the present invention are shown in Table 1:
[0062]
[0063] The synthesis process of the key intermediate M1 is as follows:
[0064] Step 1: Synthesis of M1-1:
[0065] Operation process: Under an inert atmosphere, 2-chlorophenyloxazole (307g, 2.0mol), 4-chlorophenylboronic acid (328g, 2.1mol) were added to a 10L three-necked flask. THF 4L, H2O1L, K2CO3 (553g, 4.0mol) were added and stirred and heated to 40°C. After the solution clarified, Pd(PPh3)4 (46g, 0.04mol) was added. After the addition was complete, the reaction solution was heated to 80°C and the reaction was continued for 12h until the reaction was complete. The reaction solution was cooled to room temperature and extracted with EA several times. The organic phases were combined, dried over anhydrous magnesium sulfate, filtered, and passed through a silica gel column. The product was concentrated to obtain 367g of a white solid M1-1 with a yield of 80%, an HPLC content of 98%, and a molecular weight of 230.02 according to LC-MS.
[0066] Step 2: Synthesis of M1-2:
[0067] Operation process: Under an inert atmosphere, add M1-1 (367 g, 1.6 mol), bipyralidoboric acid pinacol ester (488 g, 1.92 mol), potassium acetate (314 g, 3.2 mol), and 10 L of 1,4-dioxane into a 20 L three-necked flask. After stirring, heat the mixture to 60-65 ° C and add Pd (dppf) Cl2 (13.1 g, 0.016 mol). Then continue to heat the mixture to reflux for 6-8 hours until M1-1 reacts completely. The reaction solution was directly filtered, the filtrate was collected, concentrated under reduced pressure to dryness, dissolved in 2000 mL of toluene, and then washed with water. The organic phase was dried over anhydrous magnesium sulfate, filtered and concentrated. After the organic phase was passed through a silica gel column, the column liquid was again concentrated under reduced pressure until solid precipitated and then stopped. The temperature was lowered to 10-15°C. After crystallization was completed, it was filtered and dried to obtain a white solid M1-2406 g with a yield of 79%, an HPLC content of 99%, and an LC-MS molecular weight of 322.12.
[0068] Step 3: Synthesis of M1-3:
[0069] Operation process: Under an inert atmosphere, M1-2 (401g, 1.25mol), 2,6-dibromo-4-chloropyridine (163g, 0.60mol), 1,4-dioxane 4000mL, potassium carbonate (345g, 2.5mol), deionized water 300mL, Pd (PPh3) 4 (29g, 0.025mol) were added to a 10L three-necked flask, and the system was heated to reflux for 18h until the reaction was complete. The reaction solution was washed with water and separated, and the organic phase was collected after passing through a diatomaceous earth funnel. The filtrate was concentrated under reduced pressure to obtain a solid crude product. 2000mL of ethanol was added for dispersion and beating, and then filtered to obtain 412g of an off-white solid M2, with a yield of 66%, an HPLC content of 99%, and an LC-MS molecular weight of 500.06.
[0070] Step 4: Synthesis of M1:
[0071] Operation process: Under an inert atmosphere, M1-3 (400g, 0.8mol), 4-chlorophenylboronic acid (131g, 0.84mol), 4L of THF, 1L of H2O, and K2CO3 (442g, 3.2mol) were added to a 10L three-necked flask. The mixture was stirred and heated to 40°C. After the solution clarified, Pd(PPh3)4 (18g, 0.016mol) was added. After the addition was complete, the reaction solution was heated to 70°C and the reaction was continued for 12h until the reaction was complete. The reaction solution was cooled to room temperature and extracted with EA several times. The organic phases were combined, dried over anhydrous magnesium sulfate, filtered, concentrated, and passed through a silica gel column to obtain 359g of M1 as a white solid, with a yield of 78%, an HPLC content of 99%, and a molecular weight of 576.10 according to LC-MS.
[0072] The synthesis of intermediates M2 to M27 all followed the synthesis process of M1.
[0073] Synthesis of compound 1-1:
[0074]
[0075] Operation process: Under an inert atmosphere, M1 (4.9 g, 0.01 mol), carbazole (2.4 g, 0.01 mol), and 50 mL of toluene were added to a 100 mL three-necked flask and stirred until the solution was clear. Pd2(dba)3 (0.18 g, 0.2 mmol), Am-phos (0.13 g, 0.5 mmol), and sodium tert-butoxide (1.9 g, 0.02 mmol) were added, and the reaction solution was heated to 120 ° C and the reaction was continued for 10 h. After the reaction was completed, diatomaceous earth was used for hot filtration, the filtrate was cooled to room temperature, and purified water was added for washing. After separation, the organic phase was retained, and the aqueous phase was extracted with ethyl acetate. The organic phases were combined, dried over anhydrous magnesium sulfate, concentrated, and passed through a column to obtain compound 1-1 as an off-white solid, 6.1 g, a yield of 76%, an HPLC content of 99%, and a molecular weight of 707.16 shown by LC-MS.
[0076] Synthesis of compound 1-133:
[0077]
[0078] Operation process: The synthesis process of compound 1-133 refers to the synthesis process of compound 1-1, and M3 (6.6 g, 0.01 mol) and N-phenyl-2-benzidine (2.5 g, 0.01 mol) are added to obtain an off-white solid, 6.3 g, with a yield of 73%, HPLC content of 99%, and LC-MS showing a molecular weight of 867.32.
[0079] The synthesis of other compounds all referred to the synthesis process of compound 1-1.
[0080] The key starting materials used in the present invention are summarized in Table 2:
[0081]
[0082]
[0083] Figure 2 is the NMR spectrum of compound 1-1 of the present invention; Figure 3 is the nuclear magnetic spectrum of compound 2-19 of the present invention; Figure 4 is the NMR spectrum of compound 2-59 of the present invention.
[0084] The process of the organic electroluminescent device embodiment is described as follows:
[0085] Based on one of the above organic electroluminescent compounds, a bipolar host luminescent material is used as the luminescent layer in the test device, wherein the basic structure and preparation method of the device adopt conventional device preparation process technology. The device structure diagram is shown in FIG. Figure 1 As shown in the figure, the method for making the test device is described in detail as follows:
[0086] Schematic diagram of the test device structure of the experimental process of the present invention ( Figure 1 ) is described as follows: a polymer substrate 1, an anode layer 2 (ITO conductive glass), a hole injection layer 3 material (HIL), a hole transport layer 4 (HTL), an electron blocking layer 5 (EBL), an emitting layer 6 (EML), a hole blocking layer 7 (HBL), an electron transport layer 8 (ETL), an electron injection layer 9 (EIL), a cathode layer 10 (Mg (10%)-Al (90%) alloy) and a high refractive index cover layer 11. These 11 parts are composed, wherein the organic electroluminescent compound of the present invention is used in the emitting layer (EML) as a bipolar host luminescent material for evaluation experimental process. The detailed device preparation process is briefly described as follows:
[0087] A certain thickness of indium tin oxide is adhered to a polymer substrate with high mechanical strength, excellent thermal stability, excellent water resistance and excellent transparency as an anode. The polymer substrate is pretreated and cleaned in advance, and then different functional layers and organic functional layer materials of set thickness are sequentially evaporated according to the above structural characteristics. After the electron injection layer material is evaporated, a magnesium-aluminum alloy cathode is sputtered at a low temperature. After the cathode sputtering is completed, a layer of high-refractive index covering layer material is evaporated to improve the refractive index of the cathode surface and increase the light extraction rate. Finally, the test device is packaged using conventional device testing and packaging methods to complete the entire production process of the test device.
[0088] Preferably, the anode is usually a material with a large work function in order to enable holes to be smoothly injected into the organic layer. Anode materials that can be used in the present invention include: indium tin oxide (ITO), indium zinc oxide (IZO), tin dioxide (SnO2), zinc oxide (ZnO), etc.
[0089] Preferably, the cathode is usually a material with a small work function in order to facilitate the injection of electrons into the organic layer. The cathode materials that can be used in the present invention include: magnesium (Mg), silver (Ag), aluminum (Al), aluminum-lithium (Al-Li), calcium (Ca), magnesium-indium (Mg-In), magnesium-aluminum (Mg-Al) and other metals or alloys and organic combinations thereof.
[0090] The organic functional layer is distributed between the cathode and the anode, and specifically includes a hole injection layer, a hole transport layer, an electron blocking layer, a light-emitting layer, a hole blocking layer, an electron transport layer, and an electron injection layer; the light-emitting layer is located between the electron blocking layer and the hole blocking layer, and other functional layer materials are selected from corresponding functional layer materials with excellent cost-effectiveness in the industry to prepare test devices. The compatibility between the various functional layers needs to be determined through a series of tests and screening processes.
[0091] The functional organic layer can be formed on the electrode by various means or methods such as vacuum thermal evaporation, spin coating, printing, etc. The compounds used as each organic layer except the light-emitting layer can be organic small molecules, organic macromolecules and polymers, and combinations thereof.
[0092] The light-emitting layer (EML) is co-evaporated by a composite form of a host and a guest light-emitting material, the host light-emitting material is selected from the organic electroluminescent compound of the present invention, and the guest light-emitting material is selected from the phosphorescent material. In this case, the composite ratio of the two is 98:2. Similarly, a sensitizer material can be further added to optimize the structure of the light-emitting layer. In this case, the main light-emitting material is selected from The host luminescent material is selected from one of the phosphorescent materials DP-1, DP-2, and DP-3, and the sensitizer is selected from one of the organic electroluminescent compounds of the present invention. The host luminescent material, sensitizer, and guest luminescent material are used in a mass ratio of 98:0.1:2. After the functional layers are evaporated, they are finally packaged using the device packaging method commonly used in the industry. The samples used as test devices are prepared into 30mm×30mm samples, and the various luminescence performance indicators of these samples are then tested. Compared with test devices prepared with existing commonly used host luminescent materials, the test devices prepared with the preferred compounds of the present invention have a longer lifespan when the luminescence brightness is consistent, and higher brightness at the same test voltage.
[0093] The details of device preparation are as follows:
[0094] Device Comparative Examples 1 to 6:
[0095] The organic electroluminescent device was prepared by the following steps:
[0096] like Figure 1As shown, the polymer substrate 1 (polyethylene terephthalate (PET) plastic 1.5mm); the anode layer 2 (indium tin oxide ITO 0.15mm), is washed before use, i.e., sequentially subjected to alkaline washing, pure water washing, drying, and then ultraviolet-ozone washing to remove organic residues on the surface of the anode layer. On the washed anode layer 2, a vacuum evaporation device is used to evaporate a 20nm thick MoO3 film as a hole injection layer 3 (HIL); then a 45nm thick hole transport layer 4 (HTL) is evaporated, and the material can be selected from HT-1, HT-2, HT-3 (HT-3 was selected in this test); then a 30nm thick electron blocking layer 5 (EBL) is evaporated, and the material is selected from one of EB-1, EB-2, EB-3 (EB-3 was selected in this test); and further evaporation is continued on the electron blocking layer 5. The light-emitting layer 6 (EML) is plated, the main light-emitting material of the light-emitting layer is selected from one of H1, H2, and H3 (Comparative Examples 1 to 3), the guest light-emitting material is selected from one of DP-1, DP-2, and DP-3 (DP-1 is selected in this case), and the main light-emitting material and the guest light-emitting material are co-evaporated at a mass ratio of 98:2 to complete the process, and the thickness of the light-emitting layer is controlled to be 60 nm; furthermore, the main light-emitting material of the light-emitting layer is selected from H2, the guest light-emitting material is selected from DP-1, and the sensitizer is selected from compounds S-7, S- 49, S-50, one of S-58 (S-7, S-49 are selected in this embodiment), and the host light-emitting material, sensitizer, and guest light-emitting material are co-evaporated in a mass ratio of 98:0.1:2 to complete (Comparative Examples 4-5), and the thickness of the light-emitting layer is controlled to be 60nm; a 10nm thick hole blocking layer 7 (HBL) is continuously evaporated on the light-emitting layer, and the material is selected from one of HB-1 and HB-2 (HB-1 is selected in this embodiment); then a 30nm thick electron transport layer 8 (ETL) is continuously evaporated, The material is selected from one of ET-1, ET-2, and ET-3 (ET-2 is selected in this embodiment); a 16nm electron injection layer 9 (EIL) is continuously evaporated on the electron transport layer 8, and the material is selected as LiF; after the electron injection layer 9 is evaporated, a 10nm thick Mg-Al (Mg:Al=1:9) alloy is sputtered as a cathode by low-temperature sputtering, and finally a 40nm thick covering layer 11 is continuously evaporated on the cathode, and the material is selected as CPL; finally, the above functional layers are vacuum packaged, and the device is completed.
[0097] Detailed preparation scheme of device comparative examples 1 to 6:
[0098] Comparative Example 1: PET substrate / ITO / MoO3 (20 nm) / HT-3 (45 nm) / EB-3 (30 nm) / H1:DP-1=98:2 (60 nm) / HB-1 (10 nm) / ET-2 (30 nm) / LiF (16 nm) / Mg:Al=9:1 (10 nm) / CPL (40 nm);
[0099] Comparative Example 2: PET substrate / ITO / MoO3(20nm) / HT-3(45nm) / EB-3(30nm) / H2:DP-1=98:2(60nm) / HB-1(10nm) / ET-2(30nm) / LiF(16nm) / Mg:Al=9:1(10nm) / CPL(40nm);
[0100] Comparative Example 3: PET substrate / ITO / MoO3 (20 nm) / HT-3 (45 nm) / EB-3 (30 nm) / H3:DP-1=98:2 (60 nm) / HB-1 (10 nm) / ET-2 (30 nm) / LiF (16 nm) / Mg:Al=9:1 (10 nm) / CPL (40 nm);
[0101] Comparative Example 4: PET substrate / ITO / MoO3 (20 nm) / HT-3 (45 nm) / EB-3 (30 nm) / H2:S-7DP-1=98:2:0.1 (60 nm) / HB-1 (10 nm) / ET-2 (30 nm) / LiF (16 nm) / Mg:Al=9:1 (10 nm) / CPL (40 nm);
[0102] Comparative Example 5: PET substrate / ITO / MoO3 (20 nm) / HT-3 (45 nm) / EB-3 (30 nm) / H2:S-49:DP-1=98:2:0.1 (60 nm) / HB-1 (10 nm) / ET-2 (30 nm) / LiF (16 nm) / Mg:Al=9:1 (10 nm) / CPL (40 nm);
[0103] Detailed preparation scheme of the embodiment of the present invention:
[0104] Example 1 to Example 12:
[0105] The device preparation process was carried out according to the method of device comparison example 1, except that the preferred compounds 1-19, 1-156, 1-233, 1-237, 2-19, 2-156, 2-233, 2-237, 3-19, 3-156, 3-233, and 3-237 described in the present invention were used as the main luminescent materials of the luminescent layer, and the guest luminescent material used in combination was DP-1.
[0106] Example 13 to Example 16:
[0107] The device preparation process was carried out according to the method of device comparative example 4, except that the preferred compounds 2-19, 2-156, 2-233, and 2-237 of the present invention were used as sensitizers, the main luminescent material used was H2, and the guest luminescent material used was DP-1.
[0108] The structure of each functional layer of the above-mentioned test device is summarized in Table 3 below.
[0109] Table 3
[0110]
[0111] The functional layer materials involved in the above device preparation process can be selected from one or more combinations of corresponding functional layer materials. During the device implementation process, the specific structure of each functional layer is described as follows:
[0112] The sensitizer materials are as follows:
[0113] The HTL functional layer can be selected from the following materials:
[0114]
[0115] The EBL functional layer is selected from the following materials:
[0116]
[0117] The HBL functional layer materials are as follows:
[0118]
[0119] The ETL functional layer materials are as follows:
[0120]
[0121] The covering materials are as follows:
[0122]
[0123] The performance test data of the multilayer composite structure test device and the control device prepared using the compound of the present invention are summarized in Table 4 below:
[0124] Table 4
[0125]
[0126]
[0127] As shown in Table 4 above, from the test data, under the same device manufacturing process conditions, under the same current density conditions, the device performance was tested. The test device prepared by using the preferred compound of the present invention as the bipolar host luminescent material had a reduced roll-off efficiency, a maximum increase of 42% in current efficiency, a maximum increase of 57% in LT95 life, and an increase of more than 43% in external quantum efficiency. When the device prepared after adding the sensitizer, the roll-off efficiency was significantly reduced, and the current efficiency, device life, and maximum external quantum efficiency were also significantly improved. This shows that the preferred compound of the present invention is used as a bipolar host material or sensitizer in the light-emitting layer of the OLED device, and the comprehensive luminous efficacy is significantly improved. The devices prepared with compounds 1-19, 2-19, and 3-19 (symmetrical compounds) have a slightly lower comprehensive luminous performance than the devices prepared with compounds 1-156, 1-233, 1-237, 2-156, 2-233, 2-237, 3-156, 3-233, and 3-237 (asymmetric compounds) in other examples, which shows that reducing the molecular symmetry helps to improve the device luminous performance. The devices prepared using the 2-series compounds (mother core: pyrimidine skeleton) have significantly better luminescence performance than the 1-series compounds (mother core: pyrimidine skeleton) and the 3-series compounds (mother core: triazine skeleton). This is because the pyrimidine skeleton can better balance holes and electrons in the light-emitting layer, thereby improving the luminescence efficiency.
[0128] The present invention uses azabenzene (pyridine, pyrimidine, triazine) as the parent core structure, and symmetrically introduces fixed substituents on both sides of the parent core (azabenzene), such as phenyl-benzoxazole, phenyl-benzothiazole, phenyl-benzimidazole, phenyl-indole, phenyl-benzoquinoxaline, phenyl-phenanthroline, phenyl-pteridine, etc. This design not only achieves efficient control of the LUMO and HOMO energy levels of the molecule, but also ensures the structural stability of the molecule and effectively regulates the internal energy level distribution of the molecule.
[0129] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in this field without departing from the scope of the present invention.
[0130] Many other changes and modifications can be made without departing from the spirit and scope of the present invention. It should be understood that the present invention is not limited to the specific embodiments, and the scope of the present invention is defined by the appended claims.
Claims
1. An organic electroluminescent compound, characterized in that: The general structural formula of the organic electroluminescent compound is shown in general formula 1: in, A and B are independently selected from H, C6-C 40 Aryl or C4~C 40 A and B cannot be selected from H at the same time; X is selected from O atom, S atom, substituted or unsubstituted N atom, substituted or unsubstituted C atom; Z1, Z2, Z3 are independently selected from C atom or N atom, and there is at least one N atom among Z1, Z2, Z3; L1, L2, L3 are each independently selected from a bond or a phenylene group; Y1 and Y2 are independently selected from C6 to C 20 Heterocyclic aromatic hydrocarbons; The bonding mode between A and B and the main structure is single bond or ring bonding; The ring structures corresponding to A and B are called ring A and ring B, respectively; n is 0 or 1. When n is 0, ring A and ring B are directly bonded to each other via a single bond or are not bonded to each other.
2. An organic electroluminescent compound according to claim 1, characterized in that: The general formula 1 includes general formula 1-1, general formula 1-2, general formula 1-3, general formula 2-1, general formula 2-2 and general formula 2-3, and the specific general formula is as follows: In general formula 1-1, general formula 1-2 and general formula 1-3, the wavy line It means that ring A and ring B are directly bonded to each other via a single bond or are not bonded to each other.
3. An organic electroluminescent compound according to claim 1, characterized in that: The Y1 and Y2 are independently selected from the following groups:
4. An organic electroluminescent compound according to claim 1, characterized in that: The organic electroluminescent compound is selected from any one of the following compounds:
5. An organic electroluminescent device, characterized in that: The organic electroluminescent device comprises a cathode, an anode and an organic layer located between the cathode and the anode, wherein the organic layer comprises a hole transport layer, a light-emitting layer and an electron transport layer, wherein the light-emitting layer comprises a host light-emitting material and a guest light-emitting material, wherein the host light-emitting material comprises any one of the organic electroluminescent compounds described in any one of claims 1 to 4; and the ratio of the host light-emitting material to the guest light-emitting material is 97:3 to 99:
1.
6. The organic electroluminescent device according to claim 5, characterized in that: The light-emitting layer comprises a main light-emitting material, a guest light-emitting material and a sensitizer material, wherein the sensitizer material comprises any one of the organic electroluminescent compounds described in any one of claims 1 to 4; the mass ratio of the main light-emitting material, the sensitizer and the guest light-emitting material is 98:0.1:
2.
7. The organic electroluminescent device according to claim 5, characterized in that: The guest luminescent material is selected from any one of the following structures:
8. The organic electroluminescent device according to claim 5, characterized in that: The main luminescent material is selected from any one of the following structures:
9. The organic electroluminescent device according to claim 5, characterized in that: The usage ratio of the main luminescent material to the guest luminescent material is 98:
2.
10. The organic electroluminescent device according to claim 5, characterized in that: The organic electroluminescent device is applied to the fields of luminous illumination, image display or photoelectric signal transmission.